Persepsi Mahasiswa Program Studi Pendidikan Ekonomi FKIP Universitas Muhammadiyah Bengkulu Terhadap Pelaksanaan Perkuliahan Secara Daring - Suharmi Suharmi; Piya Henita (Jurnal Multidisiplin Dehasen (MUDE), 2022)
This study aims to determine the perception of students of the economic education study program at the University of Muhammadiyah Bengkulu on the implementation of online lectures. This research is a quantitative descriptive study. The data collection used in this research are Observation, Questionnaire / Questionnaire, and Documentation, and percentage data analysis techniques. The results of this study indicate that the perception of students of the Economic Education Study Program FKIP University of Muhammadiyah Bengkulu against the implementation of online lectures does not agree with the percentage of 64.36% being in the interval 52-67 with a total sample of 50 respondents from semester 3, semester 5, and semester 7. In the implementation of online lectures during the covid-19 pandemic, many factors became obstacles, especially the inadequate signal factor, the less conducive home atmosphere, and the need for sufficient quota.